Growth of Large-Area SnS Films with Oriented 2D SnS Layers for Energy-Efficient Broadband Optoelectronics - Patel, Malkeshkumar; Kim, Joondong; Kim, Yu Kwon (Advanced Functional Materials, 2018)
The anisotropic properties of 2D orthorhombic SnS (tin monosulfide, p-type) layers can be utilized in energy-efficient optoelectronics by growing 2D SnS layers with a preferred orientation. To meet such a need, a strategy for growing SnS layers with the control of structural parameters such as orientation and thickness is highly desired. This report demonstrates a simple procedure for growing a large-area SnS thin film composed of nanoscale SnS platelets with a controlled orientation relative to the surface via a single-step process involving in situ sulfur depletion and phase structural transition of the sputter-deposited SnS2 particles. The synthesized SnS films show good optoelectronic performances such as high signal-to-noise ratios, linear dynamic range, and high response speeds. In addition, the orientation of the SnS platelets is found to control the optoelectronic properties such as the electronic junction formation and the optical reflectance. The orientation-controlled SnS layers on Si substrate operate as a good photosensor with a good zero-bias photoresponse over a wide range of wavelengths including ultraviolet, visible, and near-infrared. The device performances evaluated from the transient photovoltage, photocurrent, Mott–Schottky characteristics, and impedance spectroscopy are all well correlated with the geometric orientation of the 2D SnS layers within the film.
Keywords: Anisotropic material properties; Energy efficient; High signal-to-noise ratio; Monosulfide; Optoelectronic properties; Schottky characteristics; Structural transitions; Transient photovoltage; anisotropic material properties; broadband photodetectors; energy-efficient optoelectronics; phase structural transitions; tin monosulfide